Priorities of geopolitics in the context of the crisis of the unipolar world - Antonovich, Ivan I. (Journal of the Belarusian State University. Sociology, 2024)
The priorities of geopolitics and geostrategy caused by global socio-economic changes are analysed. There are two fundamental long-term trends in world politics: according to the first trend, the interests of the whole world should coincide with the interests of the United States of America, according to the second trend, a just society should be built in which power belongs to the people. The confrontation of these trends underlies the global conflict and has a significant impact on the formation of a new world order. It is noted that today, pan-Atlantists cannot be expected to make serious changes in their attitude towards Russia and its allies. Multicentricity, the contours of which are becoming increasingly clear, can only be achieved through a long and persistent international struggle. The main thing is that the conflicts arising in the course of this struggle do not escalate into a global nuclear clash. The most important geopolitical task and priority of world politics is to force the United States of America to cooperate on the fundamental problems of the development of the modern world. The main one among these problems is the salvation of the natural environment, which can be ensured only through international cooperation, in which the United States of America, China and Russia should play a leading role.